Metaphorical Contracts and Games: Goethe's Götz von Berlichingen and Schiller's Fiesco. Issue 2 (2nd June 2022) - Nitschke, Claudia
Abstract: The question of how to devise and justify political order for a secular age is still at the heart of political discourse today. Social contracts provided an early political and philosophical answer to these issues, but they also manifested themselves in eighteenth-century German literature: This article will examine how Johann Wolfgang von Goethe and Friedrich Schiller engaged with the specific propositions of contractarianism (in particular Thomas Hobbes's Leviathan ) in selected scenes in Götz von Berlichingen (1773) and Fiesco's Conspiracy at Genoa (1783), respectively. In their interpretation of contractarian scenarios, Goethe and Schiller isolate the notion of utility which, they argue, reduces complex social cooperation and interaction to game-like scenarios, exclusively driven by calculation and rational decision making. Goethe's and Schiller's morally inflected deconstruction of Hobbes's thought experiment affords an insight into alternative models of social togetherness which place an emphasis on Bildung, evolution, mutuality, and recognition.